Longitudinal Vestibular and Oculomotor Impairments Among Amateur Athletes 1 Year Following Sport-Related Concussion: A Prospective Follow-Up. Issue 2 (5th March 2022) - Büttner, Fionn; Howell, David R.; Doherty, Cailbhe; Blake, Catherine; Ryan, John; Delahunt, Eamonn
Abstract : Objectives: To investigate (i) the presence of vestibular and oculomotor impairments and (ii) the self-perceived effects of concussion-associated dizziness on health-related quality of life among amateur athletes 6 months and 1 year following sport-related concussion compared with nonconcussed, control athletes. Design: Prospective, matched-cohort study. Setting: Clinical assessment laboratory. Participants: Amateur athletes who were diagnosed with sport-related concussion within 1 week of injury, and sex-, age-, and activity-matched nonconcussed, control athletes. Main Measures: Participants were evaluated 6 months and 1 year following sport-related concussion and enrollment in the longitudinal study using the Vestibular and Oculo-Motor Screening and the Dizziness Handicap Inventory. We performed multivariate analyses of variance and chi-square analyses to compare concussion and control group scores at each study assessment. Results: Forty-seven participants with concussion and 47 control participants completed the study. The concussion group reported similar mean symptom provocation scores on the Vestibular and Oculo-Motor Screening and exhibited a similar near-point convergence distance compared with the control group at the 6-month and 1-year study assessments. The concussion and control groups had similar perceptions of the effects of dizziness on their health-related quality of life at both study assessments. Conclusion: Meaningful differences in vestibular and oculomotor symptom provocation and self-perceived effects of dizziness on everyday life were not observed between concussed and nonconcussed, control athletes 6 months and 1 year following sport-related concussion.